O uso de aplicativos digitais na comunicação dos surdos: estudo de caso sobre suas preferências - Matsubara, Sibele Sachie (2018)
This study brings together contributions on the preferences of deaf people in relation to communicative applications. In order to carry out this research, it was important to understand in more depth the community of people who are hearing impaired, who have their own language, Brazilia Sign Language (GESSER, 2009) and have a different identity and culture from hearing people (GOES et al, 2011). Although many actions (including benefits, laws and public policies) take place due to the approach of deafness from the perspective of what is deficient in it – lack o hearing -, this study brings the discussion regarding the socio-anthropological view of deafness, based on the difference and not on the disability (SKLIAR, 1998; 2004). It is worth mentioning the influence of language in this context, shaping the deaf person and his or her choices. This project also carried out a survey which listed and analysed the technologies that assist deaf people’s communication, introducing the applications to be approached in the research done with a group of deaf people. The interviews brought a variety of contributions, among which we highlight: a list of suggestions for improving the applications, the level of satisfaction of the group of respondents with the most used applications and details about what motivates them to use the apps and their main functionalities